Masking of endotoxin in surfactant samples: Effects on Limulus-based detection systems. Issue 5 (September 2016) - Reich, Johannes; Lang, Pierre; Grallert, Holger; Motschmann, Hubert
Abstract: Over the last few decades Limulus Amebocyte Lysate (LAL) has been the most sensitive method for the detection of endotoxins (Lipopolysaccharides) and is well accepted in a broad field of applications. Recently, Low Endotoxin Recovery (LER) in biopharmaceutical drug products has been noticed, whereby the detection of potential endotoxin contaminations is not ensured. Notably, most of these drug products contain surfactants, which can have crucial effects on the detectability of endotoxin. In order to analyze the driving forces of LER, endotoxin detection in samples containing nonionic surfactants in various buffer systems was investigated. The results show that the process of LER is kinetically controlled and temperature-dependent. Furthermore, only the simultaneous presence of nonionic surfactants and components capable of forming metal complexes resulted in LER. In addition, capacity experiments show that even hazardous amounts of endotoxin can remain undetectable within such formulation compositions. In conclusion, the LER phenomenon is caused by endotoxin masking and not by test interference. In this process, the supramolecular structure of endotoxin is altered and exhibits only a limited susceptibility in binding to the Factor C of Limulus -based detection systems. We propose a two-step mechanism of endotoxin masking by complex forming agents and nonionic surfactants.